Livelihood Strategies as Responses to Water Availability in Pusur Subwatershed, Bengawan Solo - Rathna Wijayanti; Muhammad Baiquni; Rika Harini (Universitas Muhammadiyah Surakarta, 2016)
Water availability has a significant role on human life, particularly for the rural, agrarian communities. This study aimed to investigate the diverse conditions of water availability in Pusur sub-watershed, Bengawan Solo watershed, and the livelihood strategies of the local community in responding to the water availability. The study used both quantitative and qualitative methods of data analysis, and the data was collected through questionnaire, in-depth interview, and observation. On the water availability, the study used the following variables: (1) quality, (2) quantity, (3) spatial and temporal distribution, (4) access, (5) social-economy, and (5) institutional aspect. On the livelihood strategies, it uses: (1) reaction and (2) anticipation for water deficit. In term of sampling methods, the study used area and purposive sampling, by splitting the study site into the upper, middle, and lower area. The analysis of this study indicates that the level of water availability in the upper area is considered low. The community living in the upper area depends upon rainwater for its agricultural sector, and upon the water supply distributed by pipelines and tanker trucks for its household. The study also indicates that the middle area has abundant water supply, but the quality has been declined due to pollution, poor sanitation system, and potential conflict among the community members. Meanwhile, in the lower area, particularly in the dry season, irrigation water has been inadequate. Responding to the diverse water availability, the community has applied the following livelihood strategies: (1) leaving the agricultural land uncultivated in the upper area, and (2) pumping wells and rivers in the middle and lower areas. In addition, as part of its precautions actions, the community has applied: (1) agroforestry system at the upper area, (2) improved the irrigation system of the middle area, and (3) creating wells and using water pumps in the lower area.